Decisão judicial, expectativas e estabilização social: repensando a legitimação pelo procedimento na sociedade complexa - Webber, Suelen da Silva (Universidade do Vale do Rio dos Sinos, 2015)
This research argues that, in a social dynamics that needs stability to evolve and support itself, Luhmann's Legitimation by Procedure can still be considered an effective element in order to restrain disappointments which may affect either Social System and Psychic System. But this would be possible only if reread by autopoiesis, and thought as a structure, which needs other elements to fulfill this stabilizing function. Among them, the reasoning in patterns outlined in this thesis, and the meaning that, together, will lead them to a learning process. In this setting of social communications in which the judicial decision seems to have assumed the center of citizens' expectations, as several issues concearning everyday life are took to Judiciary to be solved, new expectations are created, disappointments and expectations of expectations that, if not well managed, may cause irritations e collapses in systems. As long as the judicial decision becomes more important in the Society of communications, to observe the judge's and organization's role on taking decisions process is needed, once a Society is characterized by the excess of possibilities, that is, by the fact that there are much more possibilities that it is possible to experience or to see, there is no way to think of social stabilization and disappointments channelling through the attempt of foreseeing the decision's outcome. The decision, to be valid, must bring in itself only one certainty, that there will be a decision, nothing else. This makes us question why in a democratic country a decision must be complied, and where is its legitimacy, when arguments of power are no longer enough to answer these questions. To develop all these observations, it will be used a bibliographic research followed by empiric data, in order to exemplify the theoretical circumstances pictured, all essentially based on Niklas Luhmann's Theory of Systems.
Keywords: Expectativas; Decisão judicial; Legitimação pelo procedimento; Aprendizagem; Expectations; Judicial decision; Legitimation by procedure; Learning; ACCNPQ::Ciências Sociais Aplicadas::Direito